2008
DOI: 10.1111/j.1751-553x.2007.00966.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diagnostic reliability of different RBC indices and formulas in the differentiation of the β‐thalassaemia minor from iron deficiency in Palestinian population

Abstract: Beta-thalassaemia minor and iron deficiency are the most common causes of microcytosis and/or hypochromasia. The present study evaluates the diagnostic reliability of different RBC indices and formulas, as well as our proposed formula, in the differentiation of the beta-thalassaemia minor from iron deficiency in Palestinian population. Complete blood count (CBC) parameters of 2196 certainly diagnosed (1272 beta-thalassaemia minor and 924 iron deficiency) samples were used to evaluate the following indices and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
103
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 21 publications
5
103
3
1
Order By: Relevance
“…Lafferty et al 11 found the S&L index, MI and MCV to be valuable in distinguishing IDA and β-TT minor cases; the RDW and the E&F indices were not useful. In studies including schoolchildren in Jordan, MI, MCV ≤ 72 fl, and E&F and S&L indices correctly identified 91.6%, 82.4%, 81.3% and 62.6%, respectively, of microcytosis cases as having or not having the β-TT trait 12 . Using the Youden index, Demir et al 9 found RBC and RDWI to be of good predictive value in paediatric patients; they set the Youden index value of the S&L index to zero.…”
Section: Discussionmentioning
confidence: 99%
“…Lafferty et al 11 found the S&L index, MI and MCV to be valuable in distinguishing IDA and β-TT minor cases; the RDW and the E&F indices were not useful. In studies including schoolchildren in Jordan, MI, MCV ≤ 72 fl, and E&F and S&L indices correctly identified 91.6%, 82.4%, 81.3% and 62.6%, respectively, of microcytosis cases as having or not having the β-TT trait 12 . Using the Youden index, Demir et al 9 found RBC and RDWI to be of good predictive value in paediatric patients; they set the Youden index value of the S&L index to zero.…”
Section: Discussionmentioning
confidence: 99%
“…Various combinations of red blood cell indices have been proposed in order to allow discrimination between these hypochromic microcytic anemias. We have tried using several of these known discrimination indices [27] as well as the Youden index [28] for differential diagnosis of ID, thalassemia and combined thalassemia and ID on our data sets; unfortunately, none of them is satisfactory in discriminating the cases (data not shown). Classical diagnosis using serum ferritin or serum iron and total iron-binding capacity for diagnosis of ID and Hb and DNA analysis for identification of thalassemia should be obtained for accurate differential diagnosis of these common hypochromic microcytic disorders in the population of northeast Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several simple screening indices have been developed for differentiating between thalassemia trait and IDA [2][3][4][5][6][7][8] and more recently these were supplemented with other supposedly better performing indices [9][10][11][12][13][14] (Table 1). It is widely agreed that none of these indices is 100% sensitive or 100% specific.…”
Section: Introductionmentioning
confidence: 99%